Resolving capacity of infrared–visible sum frequency generation microscopy to address discrete structural realizations of a protein at interface. (22nd March 2016) - Volkov, Victor; Chelli, Riccardo
Abstract : In this article, we address theory and explore possible implications of infrared–visible sum frequency generation microscopy imaging for structural and orientational analysis of a single polypeptide at a phospholipid membrane interface. The suggested structural analysis is based on detection of amplitude (intensity) images specific to a single protein under a given orientation, rather than on detection of spectral dispersions of responses from orientationally averaged ensembles. To establish the principle and model implications, we perform quantum‐mechanical calculations of nonlinear responses of a pentadecapeptide helix and a penta‐pentadecapeptide helical dimer, the secondary structure of which is identical to that of gramicidin. Using properties of calculated amide I modes, we account polarization settings for the mixing fields, under the considered experimental geometry, to extract images specific to χYYY, χXYY, χXYX, χYZY, and χXYZ nonlinearities. If extracted in dependence on the angle of rotation of the sample holder, the reconstructed images provide information, which may allow identifying structure and orientation of the proteins under study. Hence, the approach may help addressing catalytic properties of proteins, whose role is to attune chemical permeability of membranes they associate with. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The article explores a new approach to probe structure and orientation of polypeptides at interfaces using infrared–visible sum frequency generation microscopy. The technique relies on quantitative analysis of distribution of amplitudes (intensities) of nonlinear responses of amide I normal modes in the image plane, detected upon anticipated correlation of protein orientation with the sample plane rotation. The technique would help addressing catalytic capacity of protein guests to attune mechanical properties and chemical permeability of membranes they associate.